(untitled) (Journal of the College of Basic Education, 2023)
The aim of this work is to study the effect of dust on the performance and efficiency of solar cells . Two solar panels were used clean and dusty each consists of 12 solar cells.The remaining challenge is to find accost-effective way to apply these principles to construct a low-cost solar cell with high and stable efficiency. Photovoltaic (PV) cells have social and commercial value only when they are used in a system to provide a service. This research has given a brief overview of the technical and economic considerations that allow the cells to provide such a service.